Actin ADP‐ribosylation at Threonine148 by Photorhabdus luminescens toxin TccC3 induces aggregation of intracellular F‐actin. (15th July 2016) - Lang, Alexander E.; Qu, Zheng; Schwan, Carsten; Silvan, Unai; Unger, Andreas; Schoenenberger, Cora‐Ann; Aktories, Klaus; Mannherz, Hans Georg
Summary: Intoxication of eukaryotic cells by Photorhabdus luminescens toxin TccC3 induces cell rounding and detachment from the substratum within a few hours and compromises a number of cell functions like phagocytosis. Here, we used morphological and biochemical procedures to analyse the mechanism of TccC3 intoxication. Life imaging of TccC3‐intoxicated HeLa cells transfected with AcGFP‐actin shows condensation of F‐actin into large aggregates. Life cell total internal reflection fluorescence (TIRF) microscopy of identically treated HeLa cells confirmed the formation of actin aggregates but also disassembly of F‐actin stress fibres. Recombinant TccC3 toxin ADP‐ribosylates purified skeletal and non‐muscle actin at threonine148 leading to a strong propensity to polymerize and F‐actin bundle formation as shown by TIRF and electron microscopy. Native gel electrophoresis shows strongly reduced binding of Thr148‐ADP‐ribosylated actin to the severing proteins gelsolin and its fragments G1 and G1–3, and to ADF/cofilin. Complexation of actin with these proteins inhibits its ADP‐ribosylation. TIRF microscopy demonstrates rapid polymerization of Thr148‐ADP‐ribosylated actin to curled F‐actin bundles even in the presence of thymosin β4, gelsolin or G1–3. Thr148‐ADP‐ribosylated F‐actin cannot be depolymerized by gelsolin or G1–3 as verified by TIRF, co‐sedimentation and electron microscopy and shows reduced treadmilling as indicated by a lack of stimulation of its ATPase activity after addition of cofilin‐1.